Local financial development and cash holdings in Italian SMEs. (December 2021) - Fasano, Francesco; Deloof, Marc
In this article, we investigate the effect of local financial development on cash holdings of Italian small and medium-sized enterprises (SMEs). Consistent with the hypothesis that local financial development reduces the need to hold precautionary cash because it facilitates access to bank debt, we find that local financial development measured by the density of bank branches in Italian provinces has a negative effect on corporate cash holdings. This effect is driven by SMEs with bank debt. Furthermore, the negative effect of local financial development on cash holdings only exists for younger and smaller SMEs, which are more likely to benefit from increased local financial development. Our work highlights that local financial development is an important driver of policies on holding cash by SMEs and is particularly relevant during crisis periods, such as the recent COVID-19 crisis.